Peran Komunikasi Verbal dan Nonverbal Guru dalam Keterlibatan Siswa Anak Usia Dini di Kelas (Studi Kasus pada PAUD Al Fina) - Anggeline Saviola Zabieno; Kusumajanti; Ana Kuswanti; Puri Bestari Mardani (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The phenomenon in the early childhood education (PAUD) classroom shows that children often fail to engage positively, such as being unfocused, undisciplined, and not socializing well. This study aims to analyze the role of verbal and nonverbal communication of PAUD teachers in student involvement at PAUD AL-FINA using student engagement theory, the concepts of purr words and snarl words, proxemics theory, and operant conditioning theory. The research method used is a descriptive qualitative approach with a case study, involving in-depth interviews and participatory observation. The data were analyzed using data reduction, coding, data presentation, and triangulation. The results show that student involvement in early childhood includes behavioral and emotional dimensions. Purr words, snarl words, and proxemics delivered by the teacher play a role in early childhood engagement in the classroom. Purr words (positive words) help improve student comfort and confidence, while snarl words (negative words) create fear and convey the negative impacts of behavior, but should be stopped because they can affect the child's social-emotional condition. Proxemics is applied to monitor, provide support, and enhance students' concentration in class. This study demonstrates that both verbal and nonverbal communication of teachers significantly contribute to student involvement, classroom management, and the social-emotional development of children.